CLIMATE CHANGE AND AGRICULTURE: EVALUATING THE IMPACT OF SUSTAINABLE WATER MANAGEMENT IN MITIGATING ENVIRONMENTAL RISKS - Arfadly, Andi Rachmat; Dimitrov, Ivan; Tuan, Samuel (Techno Agriculturae Studium of Research, 2026)
Climate change poses an existential threat to global food security, primarily through the disruption of hydrological cycles and increased frequency of extreme thermal stress. This research addresses the urgent need for adaptation by evaluating the efficacy of sustainable water management in mitigating agricultural and environmental risks. The study aims to quantify how precision irrigation and moisture-retention techniques stabilize crop yields and soil health under climatic volatility. Utilizing a three-year longitudinal experimental design across sixty agricultural sites, the methodology compared precision drip irrigation and mulching against traditional flood methods. Results indicate that integrated sustainable practices reduced water consumption by 40% while enhancing water use efficiency by over 200%. Crucially, these techniques lowered soil salinity by 60% and maintained vegetation health during peak drought periods, as evidenced by stable NDVI values. Analysis confirms that the synergy between technological precision and organic soil cover creates a robust buffer against environmental degradation. This research concludes that transitioning to sustainable water governance is a fundamental prerequisite for agricultural resilience. The findings provide a scalable framework for policymakers to de-risk food systems, asserting that nature-based hydrological infrastructure is essential for long-term ecological and economic stability in a warming world.